Pelaksanaan Pendidikan Nilai Kebangsaan Melalui Kegiatan Ekstrakurikuler Kepramukaan (Studi Kasus di SD Negeri 01 Blulukan Tahun Pelajaran 2014/2015) - Saputro, Dwi Wahyu, Drs. Mulyadi Sri Kamulyan S.H, M.Pd (2015)
The purpose of this study were: (1) To identify the values ​​of Scouting Nationality in extracurricular activities. (2) To know how to planting the National Values ​​Education through extracurricular activities Scouting. (3) describe the factors supporting and hindering implementation of the National Values ​​Education Through Scouting extracurricular activities. This research uses qualitative descriptive method, with a single case study strategy rooted, source data from an informant or informants as well as documents and archives. Informants retrieval using purposive technique. Data collection techniques in this study consisted of direct observation, interview and documentation. For the validity of the data using triangulation of data or resources from the triangulation method. Data analysis technique used is an interactive model. Based on the results of this study concluded that the implementation of national values ​​education through scouting activities in SD Negeri 01 Blulukan implemented through the planting of national and state consciousness, love of the homeland, faith in Pancasila, willingness to sacrifice for the nation and the State as well as the initial ability to defend the country. The values ​​are developed that religious values, patriotism, discipline, responsibility, national spirit, creativity, care for the environment, cooperation and courage. The additional value that appears when observations are honest, hard work, self-esteem, Self, Courtesy, Democracy, Justice. While the way that is done through exemplary, enforcement of discipline, assignments, habituation, lecture and educational games. Factors supporting the implementation of national values ​​education through extracurricular activities scouting in SD Negeri 01 Blulukan includes supporting infrastructure, in education enter the scouting as an extracurricular compulsory, quality coaches and the support of the family. While the obstacles in the implementation of national values ​​education through extracurricular activities scouting in SD Negeri 01 Blulukan consisting of internal and external obstacles. Barriers arising from internal factors, among others, a sense of fatigue because of the many children of school assignments, the limited funds activities. While the resistance of the external factors that environmental differences in character between the school environment with the surrounding communities. Keywords: National Values ​​Education, Extracurricular Scouting.